Reducción de costos en las operaciones unitarias de perforación y voladura optimizando el mantenimiento de brocas de 45mm, rimadoras de 102mm y el consumo de explosivo en las labores de desarrollo que realiza la empresa conmiciv s.a.c en cmh s.a - Abanto Cruz, Juan Omar (2016)
This work was performed in order to reduce unit costs in drilling and blasting optimizing maintenance drill 45mm, 102mm rimadoras and consumption of explosives in development work performed by the company in CMH CONMICIV S.A.C S.A. For the study we used consumption data bits, rhyming and explosives for the months of June and July without optimizing the use (before) and the months of August, September and October optimizing the use (after). In which the drill bit before and rhyming 45mm 102 Sandvik had been presenting performance 181m / drill 10% below the useful life and 172m / rhyming, 14% below the life given by the supplier Sandvik (200m) to this mine. Generating an average cost of $ 162.5 drilling / m being greater in $ / m 3.8 more drilling unit price ($ 158.7 / m), making sharpening was reached $ 156 / m this $ 6.5 / m less than Initial cost. In blasting before had an average cost of $ 106.7 / m, $ / m 2.8 more than PU blasting ($ 103.9 / m) after applying control consumption explosive it was reached to cost blasting of 96.6 $ / This $ 10.1 m / m less than initial cost. For this research the descriptive analytical scientific method is applied in the first phase was analyzed and defined the problem of high cost of drilling and blasting, with the data output bits 45mm, rhyming 102mm and quantities of explosive used in the months June and July, allowed to observe the behavior of the cost of the unit operations in two months. In the optimization phase and measurement data for the months of August, September and October it was used, we measure costs after implementation of performing maintenance sharpening drills and improved consumption of explosives. Analysis, brainstorming and improvement plan and actions to take to reduce the cost of drilling and blasting was then performed. On the Improvement phase, theoretical supervisors (foremen and guard), assistants and teachers of mine (boots) trainings were conducted. Generating savings of $ 6770.2 drilling / three months and $ 11137.7 / three months.